A new species of Labiobaetis Novikova & Kluge, 1987 (Ephemeroptera: Baetidae) from Washington, USA - Webb, J. M. (Zootaxa, 2013)
Labiobaetis sonajuventus n.sp. is described from nymphs collected in a tributary of the Okanogan River in north-central Washington, USA. The new species is distinguished from North American congeners by the well-developed keel between the bases of the antennae, the concave lateral margin of labial palp segment 2, the apically expanded submarginal setae on the labrum, and its western Nearctic distribution.